“Ega ma arsti juurde ju ometi ei lähe!” Eemiline uskmatus oletataval uue vaimsuse uurimisväljal - Age Kristel Kartau (Mäetagused, 2019)
The paper “I wouldn't go to the doctor anyway!” presents a study of alternative medicine practices among Estonians, who are allegedly the least religious people in the world. Only 6 percent of Estonians consider religion important in their lives and only 2 percent attend church weekly; 1/3 profess to never having had the experience of the sacred, and another 1/3 have difficulties expressing when and in connection with what they have felt anything being holy. One of the world’s leading researchers of New Age, Paul Heelas, has called Estonia “a golden land” for studying trajectories of changing spirituality: “over and above serving to exemplify the ‘shattering’ retreat of Christendom … Estonia calls for the transformation of the study of religion … to the comparative study of sources of significance: their various promises … or their failures”. The present study is based on 34 life-story interviews, recorded digitally in the years 2008–2019 and stored in the Estonian Folklore Archives. Although the sociological theories of religion consider alternative medicine as the New Age spirituality by default, the interviewees perceive their activity as non-religious. The label ‘New Age’ is even regarded with hostility. There are some who identify themselves as Christians, and some who see the profitability of using the Buddhist language or Taoist images, but faith per se in any religious doctrine is hard to find. Soviet ideological brainwashing during the occupation trained Estonians to hang on to thinking for themselves and antagonism-buttressed self-preservation. In a basic values survey, Estonians put autonomy and self-sufficiency (equals autarchia in church terminology) in a very high position, the third among 21 values. This defiance is visible against the church as well as the New Age ideologies, and the state medical system. This might, thus, explain the great support for heterodoxy and the cultic milieu both in the census statistics of the 21st century and the large numbers of Estonians pursuing yoga. Whoever can afford it prefers finding help in Google search and not showing up in a doctor's office. Among the interviewees there are some who use in their job such oriental body techniques as yoga, acupuncture, Thai massage, and reiki. One person is a close family member of a long-time legendary folk-healer who used forest herbs and had a reputation as a clairvoyant, but in fact had higher education in biology and chemistry and advised clients skilfully by reading chemical elements in blood tests and applying knowledge about chemical content of the plants in the home forest. One woman whose rheumatoid-arthritic daughter was treated with modern medicine without satisfactory results for many years turned to Byzantine blood-letting cupping therapy that has been practiced for centuries by Scandinavian folk medicine. After sauna suction cups are placed on the skin to force the superficial capillaries to dilate, and then skin is cut intentionally in order to cleanse the organism of toxic residues. She defines herself as believing “in nothing except in herself” – “no witchcraft whatsoever in these therapies”, according to her own words. As Bronislaw Szerszynski has noticed, feral sacrality of the split transcendental axis – “abroad natural and cultural landscape freely roaming around religious symbols and actions” – is floating in society as a free cultural resource for private use in the creation of identities. At least, something similar can be detected from some life stories in this paper: one interviewee confesses that the job of an oriental body therapist allows to “get ever closer to God, the Creator, Buddha, the Intelligent Energy – whatever it is that has created, and keeps creating the Universe and us”. By the 21st century, after breaking free from the Soviet occupation, Estonia has successfully joined not only the European and North Atlantic alliances, but likewise embraced globalisation and started eagerly to “collect exotic experiences” as a landmark of post-modernist lifestyle, according to Zygmunt Bauman. We became Westernised in an Easternised West; for vacations and career enhancement we go to Westernised East. Szerszynski's idea of the hiding place for “roaming religion” in sports, education, and medicine allows posing questions to people from the realm of belief, while totally leaving aside Christianity. I am assuming that in those explanations about why people choose one or another solution for their health or psychological problems, the “roaming religion” phenomenon expresses itself without having to ask whether a person believes in God, Intelligent Energy, self-realisation, or whatever. Thorough quantitative research is definitely needed, but first, by qualitative methods, the diverse self-describing statements should be found, by which it would be easier for us to identify ourselves.